Therapeutic neutralization of CD95-ligand and TNF attenuates brain damage in stroke - Martín-Villalba, Ana; Kleber, Susanne; Schenkel, Johannes; Krammer, Peter H. (Cell death and differentiation, 2001)
Stroke is the third most common cause of death in the Western world. The mechanisms of brain damage in the affected areas are largely unknown. Hence, rational treatment strategies are limited. Previous experimental evidence suggested that cerebral lesions were less prominent in CD95 (APO-1/Fas)-deficient (lpr) than in wild-type mice. Additional results strongly suggested that the CD95-ligand (CD95L) was a major cause of neuronal autocrine suicide in the penumbra. These data and the assumption that death-receptor systems might determine stroke-related damage in the brain prompted us to examine these systems in in vitro and in vivo models of ischemia. We showed that hybrids of TNF-deficient and gld mice were strongly resistant towards stroke-induced damage. To determine the mechanism of action of TNF and CD95L, we separately investigated their influence on primary ischemic death and secondary inflammatory injury. Inhibition of both TNF and CD95L in vitro prevented death of primary neurons induced by oxygen-glucose deprivation and reperfusion. The recruitment of inflammatory cells to the ischemic hemisphere was abrogated in the absence of both TNF and CD95L. Significantly, mice injected with a mixture of neutralizing anti-TNF and anti-CD95L antibodies 30 min after induction of stroke showed a marked decrease in both infarct volumes and mortality. Accordingly, the locomotor performance of these animals was not significantly impaired in comparison to sham-operated animals. These data reveal that inhibition of TNF and CD95L blocks stroke-related damage at two levels, the primary ischemic and the secondary inflammatory injury. These results offer new approaches in stroke treatment. Cell Death and Differentiation (2001) 8, 679-686